The hypotension prediction index in major abdominal surgery – A prospective randomised clinical trial protocol - Jakub Szrama; Agata Gradys; Zuzanna Nowak; Ashish Lohani; Krzysztof Zwoliński; Tomasz Bartkowiak; Amadeusz Woźniak; Tomasz Koszel; Krzysztof Kusza (Contemporary Clinical Trials Communications)
Background: Patients undergoing major abdominal surgery are at increased risk of developing perioperative hypotension, which is associated with increased mortality and morbidity. Despite using advanced technologies such as evaluating arterial pressure derived cardiac output, anaesthetic management to maintain hemodynamic stability is still reactive when the clinical decision is made after hypotension has developed. Previous perioperative goal-directed studies have not proven the benefits of this approach with high certainty. A new, approved technology called the Hypotension Prediction Index (HPI) aims to prevent hypotension occurrence by allowing the precise hemodynamic monitoring of patients under general anaesthesia, significantly reducing intraoperative hypotension events. This prospective randomised clinical trial aims to compare the rate of perioperative hypotension in patients undergoing major abdominal surgery according to their type of hemodynamic monitoring. Methods: and Analysis: Patients meeting the inclusion criteria will be randomly assigned to receive hemodynamic assessment with arterial pressure cardiac output (APCO) monitoring (group A) or hemodynamic monitoring with the HPI software (group B). The primary outcome is a time-weighted average (TWA) mean arterial pressure (MAP) of <65 mmHg: TWA MAP = (depth of hypotension [in mmHg] below a MAP of 65 mmHg × time [in minutes] spent below a MAP of 65 mmHg)/total duration of the operation (in minutes). Its secondary outcomes include perioperative hemodynamic management and the rate of postoperative complications. Ethics and dissemination: This trial was approved by the Ethics Committee of the Poznan University of Medical Sciences (KB–559/220; date: 01/07/2022). Its results will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT06247384.